Evaluation PAHs Contamination Level in the Breast Milk of Women in Al-Diwaniyah city, Iraq- a Case Study - Faiq F. Karam (Journal of Global Pharma Technology, 2016)
Human milk is an important bio indicator for the exposure with some pollutants like polycyclic aromatic hydrocarbons. Breast milk samples from 68 women were live in Al-Diwaniyah city were collected in this study. Thirteen of poly cyclic aromatic hydrocarbons were investigated in all samples using gas chromatography coupled with mass spectroscopy. The samples were divided into three groups according to the age range (less than 20 years, 20-30 years and 31-40 years). Eight samples were the control for this study from the rural mothers. The mothers were all them non-smokers. The samples were collected during 2017 from different regions located in Al-Diwaniyah City.Keywords: Breast milk, Polycyclic aromatic hydrocarbons, Pollution in Al-Diwaniyah City, Gas Chromatography, Exposure to pollutants.